Advances in growth factor-containing 3D printed scaffolds in orthopedics - Longwen Zhan; Yigui Zhou; Ruitang Liu; Ruilong Sun; Yunfei Li; Yongzheng Tian; Bo Fan (BioMedical Engineering OnLine)
Abstract Currently, bone tissue engineering is a research hotspot in the treatment of orthopedic diseases, and many problems in orthopedics can be solved through bone tissue engineering, which can be used to treat fractures, bone defects, arthritis, etc. More importantly, it can provide an alternative to traditional bone grafting and solve the problems of insufficient autologous bone grafting, poor histocompatibility of grafts, and insufficient induced bone regeneration. Growth factors are key factors in bone tissue engineering by promoting osteoblast proliferation and differentiation, which in turn increases the efficiency of osteogenesis and bone regeneration. 3D printing technology can provide carriers with better pore structure for growth factors to improve the stability of growth factors and precisely control their release. Studies have shown that 3D-printed scaffolds containing growth factors provide a better choice for personalized treatment, bone defect repair, and bone regeneration in orthopedics, which are important for the treatment of orthopedic diseases and have potential research value in orthopedic applications. This paper aims to summarize the research progress of 3D printed scaffolds containing growth factors in orthopedics in recent years and summarize the use of different growth factors in 3D scaffolds, including bone morphogenetic proteins, platelet-derived growth factors, transforming growth factors, vascular endothelial growth factors, etc. Optimization of material selection and the way of combining growth factors with scaffolds are also discussed.